INTROSTAT (Statistics textbook) - Underhill, Les; Bradfield, Dave (Department of Statistical Sciences, 2014)
IntroStat was designed to meet the needs of students, primarily those in business, commerce and management, for a course in applied statistics. IntroSTAT is designed as a lecture-book. One of the aims is to maximize the time spent in explaining concepts and doing examples. The book is commonly used as part of first year courses into Statistics.